Evaluation of Facial Esthetics in Rehabilitated Adults with Complete Unilateral Cleft Lip and Palate: A Comparison between Professionals with and without Experience in Oral Cleft Rehabilitation. (28th November 2012) - Almeida, Araci Malagodi; Capelozza Filho, Leopoldino; Ferrari Junior, Flavio Mauro; Lauris, Rita de Cassia Moura Carvalho; Garib, Daniela Gamba
Abstract : Objectives . The aim of this study was to evaluate the facial esthetics of White-Brazilian adults with complete unilateral cleft lip and palate (UCLP) rehabilitated at a single center. Design . 30 patients (13 females; 17 males; mean age of 24.0 years), rehabilitated at a single center, were photographed and evaluated by 25 examiners, 5 orthodontists, and 5 plastic surgeons dealing with oral clefts, 5 orthodontists and 5 plastic surgeons with no experience in the cleft treatment, and 5 laymen. Their facial profiles were classified into esthetically unpleasant, esthetically acceptable, and esthetically pleasant. Results . Orthodontists dealing with oral clefts classified the majority of the sample as esthetically pleasant. Plastic surgeons dealing with oral cleft, orthodontists, and plastic surgeons without experience with oral clefts classified most of the sample as esthetically acceptable. Laymen evaluation also considered the majority of the sample as esthetically acceptable. Conclusions . The facial profiles of rehabilitated adults with UCLP were classified mostly as esthetically acceptable, with variations among the categories of examiners. The examiners dealing with oral clefts gave higher scores to the facial esthetics when compared to professionals without experience in oral clefts and laypersons, probably due to their knowledge of the limitations involved in the rehabilitation process.